PERSEPSI MASYARAKAT TERHADAP KEBIJAKAN PENGENAAN SANKSI BIAYA PAKSA TERKAIT PENATAAN PKL DI KASAWAN KEPATIHAN KOTA BANDUNG - Reni Rachmawati; Turtiantoro .; Puji Astuti (Journal of Politic and Government Studies, 2016)
Based on the data with regard to the hawkers (pedagang kaki lima) in the city of Bandung, a few issues were discovered which currently still are the duties of Bandung government particularly in hawkers rearrangement and relocation along with the infringement behavioural of the hawkers. Starts from those issues, thus the government of Bandung has made a local regulation of Bandung No. 04 year 2011 about hawker’s rearrangement and development. Based on the local regulation, the government of Bandung does relocate the place for business for the hawkers. As it’s written in the article No. 12, the location of the hawkers is divided by three zones, there are: first, red zone is the location that is prohibited for the hawkers; second, yellow zone is the location that can be both opened and closed based on time and place; and the third, green zone is the location that allows for doing business for the hawkers. Because there are still a lot of hawkers who don’t obey the regulation which already is determined and to confirm the orderliness of the hawkers in the city of Bandung, since 1 February 2014 the government of Bandung has been applying a regulation that fines one hundred million rupiahs (Rp. 1.000.000) to the residents who go shopping in the hawkers area. The approach that is used in this research is descriptive with quantitative data analysing along with the data collection methods: questionnaire, observation, documentation, and interview. Population in this research is society (considered as consumers) who are potentially to go shopping at the red zone which is located at Kepatihan area, Bandung. Samples of this research are the societies who are potentially to go shopping at the red zone at Kepatihan area, Bandung. The determination of the sample or the respondent of the questionnaire in this research is using Isaac Michel approach in regards of the population criterion is not able to be known exactly. Sampling in this research is using accidental sampling technique. The results of the analysis of the perception of the society towards forced fee sanctions regulation at Kepatihan area related to the hawkers management in the city of Bandung can be seen in three indicators. First, cognitive indicator shows that the societies know and understand that there is forced fee sanctions regulation with the average score 64.38% which is categorised as high; second, affective indicator shows that the societies who are pleased and agree with the regulation are at average score 68.67%; and the last indicator is conative which shows that the societies feel the regulation has to be applied at Kepatihan area and will have positive impact for the societies with the average score 70.58%. 2 Based on the writer’s research, concluded that the society in the city of Bandung who were the respondents understand, support the regulation of forced fee sanctions which is applied by the government of Bandung that related to the hawkers management at the red zone, particularly at Kepatihan area. The respondents agree with the partition of prohibited zones for the hawkers in Bandung, so that when the perception of the society about the regulation is positive, thus this regulation is effective to be applied in Bandung related to the hawker’s issues. Keywords: regulation, sanctions, perception, hawkers